Development and evaluation of a hydrophilic interaction liquid chromatography‐MS/MS method to quantify 19 nucleobases and nucleosides in rat plasma. (14th November 2016) - Du, Yan; Li, Yin‐jie; Hu, Xun‐xiu; Deng, Xu; Qian, Zeng‐ting; Li, Zheng; Guo, Meng‐zhe; Tang, Dao‐quan
Abstract: As essential endogenous compounds, nucleobases and nucleosides fulfill various functions in living organisms. This study presents the development and validation of a new hydrophilic interaction liquid chromatography tandem mass spectrometry method for simultaneous quantification of 19 nucleobases and nucleosides in rat plasma. For the sample preparation, 15 kinds of protein precipitants were evaluated according to the chromatographic profile and ion response of analytes. The optimization of chromatographic separation was respectively performed using reversed‐phase liquid chromatography and hydrophilic interaction liquid chromatography mode; each separation mode included two test columns with different stationary phases. The chromatographic profile and parameters such as half‐width ( W 1/2 ), capacity factor ( K ′) and tailing factor ( f t ) were used to evaluate the separation efficiencies. Furthermore, the adopted composition of two mobile phase systems and the concentrations of the additives in the optimum buffer system were also investigated. The developed method was fully validated and successfully applied quantitatively to determine 19 nucleobases and nucleosides in plasma from normal and diabetic nephropathy (DN) rats. Significant differences between normal and DN rats were found in plasma levels of cytosine, xanthine, thymidine, adenosine, guanosine, inosine and 8‐hydroxy‐2′‐deoxyguanosine. This information may provide a useful reference for the discovery of potential biomarkers of DN.